2022
DOI: 10.12669/pjms.38.8.6927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TEAS combined with general anesthesia on early postoperative cognitive function in elderly patients undergoing single-port thoracoscopic lobectomy

Abstract: Objective: To investigate the effect of transcutaneous electrical acupoint stimulation (TEAS) on early cognitive function in elderly patients after single port thoracoscopic lobectomy. Methods: One hundred and nine patients who underwent single whole thoracoscopic lobectomy in Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine from January 2020 to October 2021 were included in this single-center, retrospective observational study. According to the treatment records, befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…MMA, defined as combining anaesthetics and analgesics with different mechanisms of action [17], aims to provide additive or synergistic pain relief while minimizing side effects associated with higher opioid doses [18]. Surgeons also support using MMA, combining general anaesthesia with regional or local anaesthesia techniques, to improve outcomes [19][20][21]. They actively contribute to postoperative MMA by employing techniques such as local infiltration or inserting surgical site catheters [2,[22][23][24].…”
Section: Why Multimodal Anaesthesia?mentioning
confidence: 99%
“…MMA, defined as combining anaesthetics and analgesics with different mechanisms of action [17], aims to provide additive or synergistic pain relief while minimizing side effects associated with higher opioid doses [18]. Surgeons also support using MMA, combining general anaesthesia with regional or local anaesthesia techniques, to improve outcomes [19][20][21]. They actively contribute to postoperative MMA by employing techniques such as local infiltration or inserting surgical site catheters [2,[22][23][24].…”
Section: Why Multimodal Anaesthesia?mentioning
confidence: 99%
“…Использование севофлурана, как и других ингаляционных анестетиков, в качестве поддержания анестезии во время операции приводит к значительному увеличению количества па циентов (до 30 %) с жалобами на послеоперационную тошноту, рвоту и озноб [60][61][62]. Кроме того, последние исследования [63][64][65] показывают, что ингаляционная анестезия ухудшает когнитивную функцию в раннем по слеоперационном периоде у лиц старше 65 лет по срав нению с использованием пропофола. В целом, являясь довольно безопасным анестетиком [66], севофлуран на сегодняшний день ограничивается только вводным нар козом у детей или клиническими ситуациями, где ис пользование пропофола противопоказано [67,68].…”
Section: выбор типа анестезииunclassified
“…This may cause significant fluctuations in hemodynamics, and increase the risk of respiratory depression and bradycardia. 5 In recent years, numerous clinical studies have shown that the injury of the affected side of the chest wall is the main source of pain in thoracoscopic lobectomy. Paravertebral nerve block can obtain unilateral banded pain relief by injecting local anesthetics at the required block plane, blocking noxious stimulation conduction, and achieving good analgesic effect.…”
Section: Introductionmentioning
confidence: 99%